2017
DOI: 10.1186/s11556-017-0175-5
|View full text |Cite
|
Sign up to set email alerts
|

Does the diurnal cycle of cortisol explain the relationship between physical performance and cognitive function in older adults?

Abstract: Background: Regular physical activity is a promising strategy to treat and prevent cognitive decline. The mechanisms that mediate these benefits are not fully clear but physical activity is thought to attenuate the harmful effects of chronic psychological stress and hypercortisolism on cognition. However, the circadian pattern of cortisol secretion is complex and it is not known which aspects are most closely associated with increased cognitive function and better physical performance. This is the first study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Previous studies have shown that a more dynamic activity of the axis (ie, a greater diurnal decline) relates to better physical performance 44 and cognitive function in older adults than does a lower activity. 45 Additionally, urinary free cortisol concentrations in the high-to-normal range are associated with an increased risk of Alzheimer’s disease. 46 Further, independent of disease, higher morning salivary cortisol concentrations in men and higher night salivary cortisol concentrations in women are associated with increased all-cause 6 to 7·5-year mortality.…”
Section: Hypothalamic–pituitary–peripheral Organ Axesmentioning
confidence: 99%
“…Previous studies have shown that a more dynamic activity of the axis (ie, a greater diurnal decline) relates to better physical performance 44 and cognitive function in older adults than does a lower activity. 45 Additionally, urinary free cortisol concentrations in the high-to-normal range are associated with an increased risk of Alzheimer’s disease. 46 Further, independent of disease, higher morning salivary cortisol concentrations in men and higher night salivary cortisol concentrations in women are associated with increased all-cause 6 to 7·5-year mortality.…”
Section: Hypothalamic–pituitary–peripheral Organ Axesmentioning
confidence: 99%
“…A number of publications have failed to report age‐related disturbances in the circadian rhythm of CORT secretion or reported increased CORT levels in aged individuals immediately after waking in the morning. [ 22,40,50,51 ] In addition, in the case of aging in humans and animals, variants of the HPA axis reaction to ASE were revealed, including a decrease in reactivity, [ 21,22,39 ] increase in reactivity, [ 9,52 ] and absence of significant age‐related change [ 22,39,52 ]…”
Section: Responsivity Of the Hpa Axis To Stress Is Dependent On The Tmentioning
confidence: 99%
“…There are very few studies analysing the effects of exercise on the diurnal cortisol secretion pattern and cognitive function with a cognitively impaired sample, and none of them includes participants with Alzheimer's disease. To the best of our knowledge, there are only three published studies in this regard, one cross-sectional ( Dijckmans et al, 2017 ) and two exercise interventions ( Baker and Frank, 2010 ; Tortosa-Martinez et al, 2015 ), which include a sample of older adults with aMCI.…”
Section: Exercise and The Diurnal Cycle Of Cortisolmentioning
confidence: 99%
“…At a cross-sectional level, Dijckmans et al (2017) showed that a greater variance in cortisol levels across the day from morning to evening was associated with better physical performance and overall cognition in a sample of healthy older adults (N = 30) and people with MCI (N = 30). No relationship was found between the CAR and cognition or physical performance.…”
Section: The Influence Of Exercise On Cognition Through Changes In Thmentioning
confidence: 99%